2005
DOI: 10.1007/s00330-005-2887-6
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-detail evaluation and dose assessment of eight digital chest radiography systems in clinical practice

Abstract: The purpose of this study was to assess contrast-detail performance and effective dose of eight different digital chest radiography systems. Digital chest radiography systems from different manufacturers were included: one storage phosphor system, one selenium-coated drum system, and six direct readout systems including four thin-film transistor (TFT) systems and two charge-coupled device (CCD) systems. For measuring image quality, a contrast-detail test object was used in combination with a phantom that simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
2
30
1
4
Order By: Relevance
“…Data were recorded at KKUH as mean ± standard error (n = 20 for each radiographic projection). these studies also concluded that flat-panel detectors achieved the best results in low-exposure imaging, followed by other DR systems such as selenium drum and CCD-based systems (Veldkamp et al, 2006;Kroft et al, 2005). A lack of implemented local/national recommendations may be another possible cause.…”
Section: Discussionmentioning
confidence: 98%
“…Data were recorded at KKUH as mean ± standard error (n = 20 for each radiographic projection). these studies also concluded that flat-panel detectors achieved the best results in low-exposure imaging, followed by other DR systems such as selenium drum and CCD-based systems (Veldkamp et al, 2006;Kroft et al, 2005). A lack of implemented local/national recommendations may be another possible cause.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors, however, concluded that 2-K hardcopy chest radiographs perform equivalently to film if adequate processing is applied [5][6][7][8]10]. Similarly it has been shown in contrast detail phantom studies that detail detectability is described insufficiently by pixel size and spatial resolution alone, but relies on a complex interaction of contrast and spatial resolution more adequately described by the modulation transfer function (MTF; [9,11,16]). …”
Section: Introductionmentioning
confidence: 91%
“…In [29,36] 0,018 0,004 -0,062 Overzichtsstudie thoraxopname PA [37] 0,015 0,007 -0,036 Thoraxopname PA, digitale toestellen [38] 0,020 0,010 -0,032 Thoraxopname PA [39] 0,020 -Abdomen AP [39] 0,22 -Cervicale wervelkolom (2 projecties) [39] 0,015 -Thoracale wervelkolom (2 projecties) [39] 0,19 -Lumbale wervelkolom [39] 0,43 -Schedel (2 projecties) [39] 0,015 -Bekken AP [39] 0,021 -Extremiteiten [39] < 0,001 -Gedetailleerde informatie over effectieve dosis bij radiologie, waaronder radiografie (handtechniek en bucky-opnamen), is beschikbaar gekomen in het demonstratieproject patiëntendosimetrie [40,41]. Dit project is uitgevoerd door het Leids Universitair Medisch Centrum in een samenwerkingsverband met elf ziekenhuizen.…”
Section: Effectieve Dosis Tijdens Radiologisch Onderzoek In Nederlandunclassified